Transformational Leadership in Family-Owned Businesses: Balancing Tradition and Innovation - Rahul Chatterjee; Priyanka Menon (ePaper Bisnis : International Journal of Entrepreneurship and Management, 2024)
This article examines transformational leadership in family-owned businesses, with a focus on balancing the preservation of traditional values and driving innovation. By conducting interviews with family business leaders and analyzing their leadership approaches, the study identifies key strategies for managing generational transitions, incorporating modern practices, and fostering organizational culture. Findings highlight that transformational leadership ensures long-term success by integrating the strengths of tradition with the opportunities of innovation.